Supplier Selection And Supplier Management Strategy An Important Strategic Decision In Manufacturing Flexibility - Loo, Cha Hing (2002)
"Competition is no longer company to company, but supply chain to supply chain". John Grossman, vice president of materials management at AlliedSignal had highlighted the strategic important of supply chain management nowadays.The rapid rate of technology change, stiff competition and globalization of market have demanded a highly flexible supply chain in order to satisfy the customer's changing expectation. Furthermore, with the increasing of outsourcing activities and shortened of product life cycles, the role of the supplier is increasingly important to the manufacturer.